Multi-modal integration of MRI and global chamber charge density mapping for the evaluation of atrial fibrillation - Alexander J. Sharp; Michael T. B. Pope; Andre Briosa e Gala; Richard Varini; Timothy R. Betts; Abhirup Banerjee (Royal Society Open Science)
Atrial fibrillation (AF) is the most prevalent clinical arrhythmia, posing significant mortality and morbidity challenges. Outcomes of current catheter ablation treatment strategies are suboptimal, highlighting the need for innovative approaches. A major obstacle lies in the inability to comprehensively assess both structural and functional remodelling in AF. Combining magnetic resonance imaging (MRI)’s detailed structural insights with global chamber charge density mapping (CDM)’s functional mapping capabilities holds promise for advancing AF management. Our research introduces a novel tool for three-dimensional reconstruction of left atrial geometries from MRI, facilitating integration into CDM systems. We comprehensively assess our tool by generating three-dimensional left atrial meshes from MRIs of eight patients with AF and compare them with the established CDM intra-chamber ultrasound approach utilizing both geometric and clinical parameters. We apply the CDM inverse algorithm to both sets of reconstructions in order to compare derived conductions across various heart rhythms and AF conduction patterns. Finally, we explore the potential utility of our integrated pipeline through an exploration of the relationship between AF conduction patterns and their proximity to adjacent thoracic structures. Ultimately, this multifaceted approach aims to unveil insights into AF mechanisms, potentially improving treatment outcomes through personalized ablation strategies targeting arrhythmogenic atrial substrate.